2023
DOI: 10.1158/1078-0432.ccr-23-1478
|View full text |Cite
|
Sign up to set email alerts
|

Negative Predictive Value of Circulating Tumor Tissue Modified Viral (TTMV)-HPV DNA for HPV-driven Oropharyngeal Cancer Surveillance

Abstract: Background: Human papillomavirus (HPV) is causally linked to oropharyngeal squamous cell carcinoma (OPSCC). Consensus guidelines recommend clinical exams and imaging in decreasing frequency as part of post-treatment surveillance for recurrence. Plasma tumor tissue modified viral (TTMV)-HPV DNA testing has emerged as a biomarker which can inform disease status during surveillance. Methods: This retrospective observational cohort study involved 543 patients who completed curative-intent therapy for HPV-associate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…21,23,44 Several recent studies using the commercial TTMV-HPV DNA assay, which was developed based on work by Chera et al, 45 reported high positive predictive values for recurrence of 95% to 100%. 19,33,34 However, despite the promise-and, pragmatically, the availability-of ctHPVDNA testing, rigorous evidence to support its widespread clinical use is still developing. The remainder of this review applies Margaret Pepe's classic 5 phases of biomarker development for early detection of cancer 46 as a framework to review the current evidence, highlight outstanding questions, and suggest research to be prioritized (Table 2).…”
Section: Conclusion and Relevancementioning
confidence: 99%
See 4 more Smart Citations
“…21,23,44 Several recent studies using the commercial TTMV-HPV DNA assay, which was developed based on work by Chera et al, 45 reported high positive predictive values for recurrence of 95% to 100%. 19,33,34 However, despite the promise-and, pragmatically, the availability-of ctHPVDNA testing, rigorous evidence to support its widespread clinical use is still developing. The remainder of this review applies Margaret Pepe's classic 5 phases of biomarker development for early detection of cancer 46 as a framework to review the current evidence, highlight outstanding questions, and suggest research to be prioritized (Table 2).…”
Section: Conclusion and Relevancementioning
confidence: 99%
“…This group conducted a follow-up study of 543 patients with commercial TTMV-HPV DNA testing. 33 Among 63 patients with recurrent disease, 55 had detectable TTMV-HPV DNA, yielding a sensitivity of 87.3%. TTMV-HPV DNA testing was the first sign of recurrence for 38 of these 55 patients (69%) with a median lead time of 53 days (range, 7-610 days).…”
Section: Current Evidencementioning
confidence: 99%
See 3 more Smart Citations